Odpowiedzi

Najlepsza Odpowiedź!
2010-01-03T19:05:37+01:00
A) (-4) * (-9)=36
b)32*(-3)=-96
c)-20*17=-340
d) - 1/4 * 2= -1/8
e)-4,2*(-5)=21
f) (-o,8)*(-500)=400
g) 1 i 2/5 * (-9/14)=-9/10
1i 2/5 zamieniamy na ułamek zwykły czyli wychodzi 7/5
h) -3 i 1/9 * 2 i 1/7= -6 i 6/9
-3i 1/9 tez zamieniamy na ułamek zwykły czyli : -28/9
2i 1/7 wychodzi nam 15/7
i) -5,4 * (-0,03)=0,162
2 3 2
2010-01-03T19:07:32+01:00
A)=36
b)=-96
c)=-340
d)=-1/4*2/1=-2/4=-1/2
e)=-42/10*(-5/1)=-210/-10=21
f)=-8/10*(-500/1)=4000/10=400
g)=7/5*(-9/14)=-63/70
h)=-28/9*15/7=-420/63
i)=-54/10*(-3/100)=162/1000=0,162
1 1 1
2010-01-03T19:09:33+01:00
A) (-4) x (-9) = 4 x 9 = 36
b)32*(-3) = (-96)
c)-20*17 = (-340)
d) - 1/4 * 2 = (0,25) x 2 = (-0,5)
e)-4,2*(-5) = 4,2 x 5 = 21
f) (-o,8)*(-500) = 0,8 x 500 = 400
g) 1 i 2/5 * (-9/14) = 7/5 x (-9/14) = (-63/70) = (-0,9)
h) -3 i 1/9 * 2 i 1/7 = (-28/9) x 15/7 = (-420/63) = (-6 2/3)
i) -5,4 * (-0,03) = 5,4 x 0,03 = 0,162

1 5 1